2019
DOI: 10.33692/avrasyad.543706
|View full text |Cite
|
Sign up to set email alerts
|

Makro Ekonomi̇k Göstergeleri̇n Endeks Geti̇ri̇leri̇ Üzeri̇ndeki̇ Etki̇si̇: Bi̇st Örneği̇

Abstract: Sermaye piyasası ile para piyasası, bir ülke ekonomisinde reel kesim ile finans kesimini oluĢturan önemli finansal piyasalardır. Bu piyasalar fon arz ve talebinin karĢılaĢtığı, tahvil, hisse senedi, döviz, altın, mevduat sertifikası, finansman bonosu gibi finansal varlıkların alınıp satıldığı piyasalardır. Finansal piyasalarda fon transferi tasarruf fazlası olan ekonomik birimlerden tasarruf açığı olan ekonomik birimlere doğru gerçekleĢmektedir. Böylece finansal sistem sayesinde piyasalarda fırsatları değerlen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The effect of exchange rates risk on stock returns showed that the traditional theory was valid in the pre-pandemic period. In this context, the results of the analysis showed parallelism with the findings of Eyüboğlu and Eyüboğlu (2018) and Durmuş et al (2019).…”
Section: 𝑅𝑀 = 𝛼0 + 𝛼1𝐿𝐾𝑈𝑅+𝜀𝑡supporting
confidence: 75%
“…The effect of exchange rates risk on stock returns showed that the traditional theory was valid in the pre-pandemic period. In this context, the results of the analysis showed parallelism with the findings of Eyüboğlu and Eyüboğlu (2018) and Durmuş et al (2019).…”
Section: 𝑅𝑀 = 𝛼0 + 𝛼1𝐿𝐾𝑈𝑅+𝜀𝑡supporting
confidence: 75%
“…They concluded that the returns of stocks are sensitive to inflation and lag values of stocks. Durmuş, Yılmaz and Şahin (2019), in the study conducted with monthly data between the periods 2006:5 -2018:10, the macroeconomic factors explaining the returns of BIST Bank and BIST Financial index were examined with the VAR method. It was stated that the gold prices and Euro exchange rate variables explained the BIST Bank and BIST Financial index returns the most, and the inflation rate variable the least.…”
Section: Literature Analysismentioning
confidence: 99%